Microplastics in and Near Landlocked Countries of Central and East Asia: A Review of Occurrence and Characteristics - Tang, Kuok Ho Daniel (Tecno Scientifica Publishing, 2023)
The detection of microplastics in the water and sediment samples of the landlocked countries in central and eastern Asia means the relatively less populous countries are not spared from microplastic pollution. It is crucial to understand the severity of microplastic pollution in and near those countries since there are significantly fewer regional studies on microplastic pollution conducted for those countries. This review aims to systematically present the occurrence and characteristics of microplastics in and near the landlocked countries to shed light on the severity of microplastic pollution therein. It analyzed the contents of more than 38 papers to achieve its aim. Of all the landlocked countries, Mongolia has the most studies on microplastic pollution, while there are none for Turkmenistan, Afghanistan, Uzbekistan, Kyrgyzstan, and Tajikistan. For dried sediment samples, the microplastic contents ranged from 862 items/kg in the Tuul River of Mongolia to 15–46 items/kg on the Iranian side of the Caspian Sea near Turkmenistan. Lake Hovsgol in Mongolia recorded a microplastic density of 20,264 items/km2, whereas the Selenga River system had a mean microplastic density of 120.14 items/km2. Microplastics concentrations in the Caspian Sea varied, with areas near the southwest of Turkmenistan having microplastics concentrations ranging from 0.000246 items/l to 0.710 items/l. The microplastics levels in the countries are comparable to those of other regions in the world, indicating the impacts of human activities on microplastic pollution. Some microplastics might also have entered the countries through long-range transport by air and water from areas of higher human activity.